2010
DOI: 10.1021/bm100619t
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Two-Layer Tantalum/Titania−Polymer Hybrid Coating

Abstract: Using a two-step procedure, radiopaque and biocompatible coatings were obtained, consisting of a tantalum layer deposited by sputtering technique and of an upper organic-inorganic hybrid layer synthesized via sol-gel. As shown by radiographic images, tantalum confers to plastic substrates good X-ray visibility, adjustable via control of deposition time, but its adhesion to the substrate is poor and manipulation easily damages the metal layer. Polymer-titania hybrid coatings, synthesized using poly-ε-caprolacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
1
11
0
1
Order By: Relevance
“…This finding is consistent with the results of Cortecchia et al [30]., who demonstrated a lack of toxic elements released by the Ta surface in culture medium. Moreover, since the rBMSCs grown in OM, Ta/OM, and Ti/OM, as well as those grown in CM, Ta/CM, and Ti/CM revealed similar ALP activity levels, and the concentrations of Ta or Ti ions were extremely low in both media, we believe that the two substrates exerted a minimal influence on cell osteogenesis through ion release.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with the results of Cortecchia et al [30]., who demonstrated a lack of toxic elements released by the Ta surface in culture medium. Moreover, since the rBMSCs grown in OM, Ta/OM, and Ti/OM, as well as those grown in CM, Ta/CM, and Ti/CM revealed similar ALP activity levels, and the concentrations of Ta or Ti ions were extremely low in both media, we believe that the two substrates exerted a minimal influence on cell osteogenesis through ion release.…”
Section: Discussionsupporting
confidence: 93%
“…X-ray images of Aluminum sheets with different thickness and that of RPU of 1 mm thickness where analyzed using Image J analysis technique to calculate the mean gray scale value. 38,39 In Figure 9, a plot of the mean gray scale value of Aluminum against its thickness is shown. It is clear that RPU of 1 mm thickness have about the same radiopacity as that of 2.7 mm thick Aluminum wedge.…”
Section: Resultsmentioning
confidence: 99%
“…11). 47,58 Results revealed that IFPCU of 200micron thickness have same radiopacity as that of 0.6-mm thick aluminum wedge and equivalent radiopacity as that of 24.2% BaSO 4 filled polyurethane (Fig. 12).…”
Section: Resultsmentioning
confidence: 92%